Literary atlas : plotting a new literary geography - Anderson, Jon, 1973- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2025)
"This book documents a new approach to literary geographies based around the Literary Atlas of Wales. It introduces an innovative 'plotted' approach which empowers reading, creates connections to localities, histories, and communities, and inspires interest in literature and geography. It showcases how literary geographies can be mobilised through the plotted approach to reading. Through documenting the Literary Atlas of Wales project, this book outlines how the plotted approach was used to engage with English language novels set in Wales. It argues that the future of this interdisciplinary subject area should be premised upon nurturing instability, turbulence, and experimentation in order to produce new insights which can change the way we understand not only the relations between literature and place, but also between other modern categories, including academic disciplines. This book will be of interest to all readers of literature, human geography, mapping, heritage studies, and tourism. It will be beneficial to those interested in the domains of cartography, creative humanities, cultural sociology, human geography, literary studies, and print cultures"--
Keywords: Geography and literature; Geography in literature; Space in literature; Literary landmarks -- Wales; Wales -- In literature; SCIENCE / Earth Sciences / Geography; SOCIAL SCIENCE / Human Geography